POLICY DESIGN OF THE REGIONAL AND CENTRAL GOVERNMENT FOR THE DEVELOPMENT OF MANDALIKA SEZ - Ferza, Ray; A. Hamudy, Moh. Ilham (Department of Government, FISIP, Universitas Padjadjaran, 2020)
The Special Economic Zone (SEZ) is one of the government’s industrial development policy. The Government established fifteen SEZ, and Mandalika Tourism SEZ is one of them. However, Mandalika’s performance was far from satisfactory. This study aimed to analyze the policies of the regional and central government in supporting the performance of Mandalika SEZ. This study used a qualitative approach by conducting interviews and focus group discussions of the stakeholders. The study found several aspects that need more attention from the government: the certainty and ease of providing incentives, community support, preparedness of organizations and institutions, and provision of special Online Single Submission (OSS)within the SEZ. The study recommended that the Ministry of Home Affairs and regional government should optimize the policies of the regional government in supporting the SEZ, such as the provision of guidelines on the central-regional incentives, affirmative actions (mainly in the empowerment of the local community), SEZ administrator institution, adjustment to the SEZ OSS that involves many regional permits, and the development of supporting areas.gb777